2016
DOI: 10.1021/acs.nanolett.6b02348
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Gate Modulation of Carrier Density and Disorder in an Oxide Two-Dimensional Electron System

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available:

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 55 publications
5
52
0
Order By: Relevance
“…Among the recently synthesized structures, the transition metal oxide superlattices (SL's), for example, play a key role, as they offer the potential for future use in devices [2]. LaAlO 3 -SrTiO 3 superlattices, for instance, have been used to fabricate diodes with with room-temperature breakdown voltages of up to 200 V [3], as well as field-effect devices [4][5][6]. Most of the compounds used in these superlattices are characterized by the presence of strong electronic correlations, that give rise to complex collective quantum phases.…”
mentioning
confidence: 99%
“…Among the recently synthesized structures, the transition metal oxide superlattices (SL's), for example, play a key role, as they offer the potential for future use in devices [2]. LaAlO 3 -SrTiO 3 superlattices, for instance, have been used to fabricate diodes with with room-temperature breakdown voltages of up to 200 V [3], as well as field-effect devices [4][5][6]. Most of the compounds used in these superlattices are characterized by the presence of strong electronic correlations, that give rise to complex collective quantum phases.…”
mentioning
confidence: 99%
“…4 show the calculated potential well, its bound states and the band dispersions along k x , for n tot = 3.39 × 10 13 cm −2 (b)-(c) and 3.59 We now turn to the effect of a backgate voltage. Empirical modeling suggests that its primary action is to control the width of the potential well, which becomes narrower with decreasing backgate voltage [28,30]. This should lead to an increased splitting between the energy levels of the states in the well [31,40,56].…”
Section: Based Onmentioning
confidence: 99%
“…This led to proposals to base the phase diagram on the sheet conductivity [24][25][26][27], which also does not provide a universal result. Almost all these experiments were done in a backgate geometry, whereas topgating has a different effect on carrier mobility [28][29][30] and on the band structure [31]. This difference is due to the opposite direction of the applied electric field, resulting in a disparate effect on the shape of the confining 2 potential well.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Schrödinger-Poisson modeling has proven itself to provide qualitative insight into experimental results (30,132) as well as predict interesting new properties of SrTiO 3 surface states. For instance, Scopigno et al reported a possible thermodynamic instability as a result of the nonlinear permittivity, in certain regions of the gate-voltage/bandoccupation phase diagram (133).…”
Section: The Self-consistent Schrödinger-poisson Frameworkmentioning
confidence: 99%